IMPROVING THE WRITING ABILITY OF THE THIRD SEMESTER ENGLISH DEPARTMENT STUDENTS AT STAIN TULUNGAGUNG THROUGH PEER ASSESSMENT - Nany Soengkono Madayani (Pusat Pengembangan Bahasa IAIN Tulungagung, 2013)
This study was designed to improve the students’ writing skills using peer assessment. It was conducted since the students had difficulties in writing, especially in generating ideas for their writing. The final purpose, it leads to the improvement of the students’ writing ability. The subjects of the study were the third semester English Department students taking Writing III. This study focused on writing problem/solution essay. The findings show that in applying peer assessment to improve the students’ writing skill, the students required to do and to get involved actively in all steps of peer assessment. Firstly, the teacher convinced the students about the importance of doing problem solving task, especially in increasing their critical thinking. Then, the procedures of writing problem solution essays as well as the model of problem solution essays as the final products of problem solving essay were explained.